Derivational Suffixes Analysis Found in “Every Summer After” Novel by Carley Fortune - Arina Dwigiyanthi, I Gusti Ayu; Nova Winarta, Ida Bagus Gde (Tell : Teaching of English Language and Literature Journal, 2024)
This study specifically concentrated on conducting an in-depth analysis of the various types of derivational suffixes. Derivational affixes were one of the most interesting topics to analyze, as they influence the formation of words from simple to complex ones. The data used in this analysis was sourced from the novel "Every Summer After" by the esteemed author Carley Fortune. Carley Fortune is a #1 Canadian national bestseller and has been honored with an award for her exceptional work as a journalist and author. This data was meticulously examined through the application of a qualitative analytical method. The research findings have been thoroughly explored using both formal and informal explanations. The analysis was based on Plag's theory (2003) and supported theory up by Carstairs-Mccarthy's theory (2002). This comprehensive approach helped in understand the findings in depth. This comprehensive linguistic analysis of the novel meticulously identified four distinct types of derivational suffixes: nominal, verbal, adjectival, and adverbial. The results revealed a notable prevalence of nominal suffixes, a total of 249 instances, and a smaller number of verbal suffixes, amounting to just 3 instances. Furthermore, this study found 96 instances of nominal suffixes, 86 instances of adverbial suffixes, and 64 instances of adjectival suffixes in the text. This thorough analysis provides a detailed examination of the intricate language intricacies found within Fortune's novel. Furthermore, it enhances the overall understanding of how derivational morphology is utilized in contemporary literature.